The Investigation of Learning Strategies of American Learners of Chinese and Japanese for Character Learning - Yamashita, Taichi; Hung, Hsiao Hsuan (Lesya Ukrainka Eastern European National University, 2016)
It has been widely recognized that Chinese and Japanese languages are exceptionally difficult to learn. One of the reasons is their logographic characters (i.e. hanzi in Chinese, kanji in Japanese) that are extremely different from alphabet-based orthography (Tong & Yip, 2015; Xu & Padilla, 2013). Accordingly, there have been research investigating how L2 learners of Chinese and Japanese deal with the difficulty by exploring learners’ strategy (Gamage, 2003; Shen, 2005). However, learning strategies for a certain aspect of characters (i.e. shape, sound) have not been investigated as much as learning strategies in general (but see Shen, 2005). In addition, there are limited longitudinal research exploring how learners change their strategies. Therefore, the researchers investigate strategies that L2 learners of American university students are using most frequently for Chinese and Japanese character learning. The study had 66 L2 learners taking either Chinese or Japanese course at an American university. They took a questionnaire at the beginning and at the end of a semester. It was found that reading, context, decomposition, rote-writing, and listening were the most frequently used strategies. Moreover, the results indicated that strategies vary depending on which aspect of characters they learn. Furthermore, learners did not change their learning strategies over three months to a notable extent.
Keywords: Chinese as a foreign language; Japanese as a foreign language; hanzi; kanji; learning strategy